TNB payment system (Billing) and customer satisfaction: a case study of TNB Banda Kaba Melaka / Solihaton Hanim Halim - Halim, Solihaton Hanim (2009)
Organizations cannot exist without customers. As such, the customer must be the central focus of the organization. The purpose of this research is to study the TNB Payment System (Billing) and Customer Satisfaction at TNB Banda Kaba Malacca. This research also will determine whether customers are satisfied with service provided by TNB Banda Kaba Malacca. In this study, the researcher collects the information from interview, observation, website and secondary data such as journal, article, annual report and text book. This study will help TNB Banda Kaba Malacca to identify their weakness in order to achieve the level of customer satisfaction toward payment system at TNB Banda Kaba Malacca. The study utilized questionnaire as the instrument for collecting data. Questionnaires have been distributed to 30 respondents. Our respondents grouped into two with 5 of them from internal staff and 25 respondents from public (customer). In conclusion some suggestion and strategies have been made to minimize the problem occur in TNB. This is important because it will improve the profit and service quality of Tenaga Nasional Berhad (TNB). From the analysis researcher have identify that the significant relationship between TNB payment system (billing) and level of customer satisfaction towards TNB staff.